PATH = a principled approach to humanitarian action - United Nations Children's Fund (Geneva : UNICEF, 2006)
It deals with subjects such as introduction to humanitarian action, international legal and ethical standards, sexual exploitation and abus e, child soldiers, armed groups, landmines, and displacement.
System requirements: Adobe acrobat professional
Keywords: Humanitarian assistance; Children's rights